Improving community disaster resilience through scorecard self-testing - Mohamed Ludin, Salizar; Arbon, Paul (Emerald Group Publishing Limited, 2017)
Purpose – The purpose of this paper is to develop government and community-level critical thinking, planning, and action for improving community disaster resilience by reporting a study that sought to evaluate the possibility of using the Torrens Resilience Institute Australian Community Disaster Resilience (CDR) Scorecard in the Malaysian context. Design/methodology/approach – A participatory action research approach (done in 2015) encouraged key people involved in managing the 2014 Kelantan floods in Malaysia’s north-east to participate in discussions about, and self-testing of, the CDR Scorecard to measure and improve their communities’ disaster resilience. Findings – The CDR Scorecard can be useful in the Malaysian community context, with some modifications. Self-testing revealed that participating communities need to strengthen their disaster resilience through better communication, cross-community cooperation, maximizing opportunities to compare their plans, actions and reactions with those reported in research publications, and aligning their community disaster management with reported best practice internationally while acknowledging the need to adapt such practice to local contexts. Research limitations/implications – There is a need for a Malaysia-wide, simple-to-use, standardized disaster resilience scorecard to improve communities’ quality, self-efficacy, and capability to facilitate improved disaster resilience. Practical implications – The adaptation of Australian CDR Scorecard for used in the country. Social implications – Awareness of CDR level will enhance community and government preparedness, mitigation, and responses to flood disaster. Originality/value – This project is the first of its kind in Malaysia. It provides an example of the possibilities of using the CDR Scorecard globally in the form of a context-specific toolkit. The engagement of key people in the community in self-testing the Scorecard provides genuine, on-the-ground, real life data, giving others an understanding of local assessment of each community’s resilience level.